Ocena kakovosti lidarja v Applovih napravah - Vipavec, Jernej (Geodetski vestnik, 2024)
In 2020, Apple incorporated a LiDAR sensor system into its smart devices, being the first to offer the laser scanning technology to the general consumer. This article investigates how a low-cost LiDAR scanning system integrated into Apple devices performs in comparison to professional geodetic terrestrial laser scanners. In addition to providing a brief overview of the functionality of the measurement system within Apple devices, a comprehensive literature review was conducted. Various authors have examined the system either in comparison to other spatial data capture methods or in studies of its applicability across different fields. In this article, we examined the geometric quality of the lidar scanning system embedded in the Apple iPad Pro device for the purpose of 3D modeling of indoor building spaces. We conducted experiments in a smaller (~1 m) and larger (~10 m) test field and evaluated the geometric quality of the captured data. The findings indicate that the Apple system cannot achieve relative positional accuracy better than 10 cm and is primarily suitable for creating informative 3D representations.
Keywords: accuracy; Apple lidar; dispersion; geodezija; iPad Pro; iPhone 13 pro; laser scanning; lasersko skeniranje; Lidar; natančnost; oblak točk; point cloud; precision; razpršenost; točnost